Morpholo: A Hologram Generator Algorithm - Canessa, Enrique; Tenze, Livio (Electronic Imaging, 2020)
We introduce the Morpholo library which is able to convert a stereoscopic snapshot into a native multi-view image through morphing and takes into account display calibration data for specific slanted lenticular monitors. Holograms are generated fast by creating Lookup Tables to replace runtime computation. The implementation of Morpholo for glasses-free streaming of live 3D video is considered.